Pandoraea oxalativorans sp. nov., Pandoraea faecigallinarum sp. nov. and Pandoraea vervacti sp. nov., isolated from oxalate-enriched culture - Sahin, Nurettin; Tani, Akio; Kotan, Recep; Sedláček, Ivo; Kimbara, Kazuhide; Tamer, Abdurrahman U (International journal of systematic and evolutionary microbiology, 2011)
Five isolates, designated TA2, TA4, TA25(T), KOx(T) and NS15(T) were isolated in previous studies by enrichment in mineral medium with potassium oxalate as the sole carbon source and were characterized using a polyphasic approach. The isolates were Gram-reaction-negative, aerobic, non-spore-forming rods. Phylogenetic analyses based on 16S rRNA and DNA gyrase B subunit (gyrB) gene sequences confirmed that the isolates belonged to the genus Pandoraea and were most closely related to Pandoraea sputorum and Pandoraea pnomenusa (97.2-99.7 % 16S rRNA gene sequence similarity). The isolates could be differentiated from their closest relatives on the basis of several phenotypic characteristics. The major cellular fatty acid profiles of the isolates comprised C₁₆:₀, C₁₈:₁ω7c, C₁₇:₀ cyclo and summed feature 3 (C₁₆:₁ω7c and/or iso-C₁₅:₀ 2-OH). On the basis of DNA-DNA hybridization studies and phylogenetic analyses, the isolates represent three novel species within the genus Pandoraea, for which the names Pandoraea oxalativorans sp. nov. (TA25(T) = NBRC 106091(T) = CCM 7677(T) = DSM 23570(T)), Pandoraea faecigallinarum sp. nov. (KOx(T) = NBRC 106092(T) = CCM 2766(T) = DSM 23572(T)) and Pandoraea vervacti sp. nov. (NS15(T) = NBRC 106088(T) = CCM 7667(T) = DSM 23571(T)) are proposed.
Keywords: Burkholderiaceae; mastné kyseliny; ribozomální DNA; DNA, Ribosomal; Fatty Acids; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; shluková analýza; Molecular Sequence Data; hybridizace nukleových kyselin; DNA gyráza; DNA Gyrase; Culture Media; oxaláty; Oxalates; Phylogeny; aerobióza; molekulární sekvence - údaje; kultivační média; Bacterial Typing Techniques; Aerobiosis; Sequence Analysis, DNA; Nucleic Acid Hybridization; techniky typizace bakterií; sekvenční analýza DNA; Cluster Analysis; fylogeneze; RNA ribozomální 16S